BUY-OUT OF PETS BECAUSE OF THEIR UNPROPER TREATMENT UNDER CIVIL LEGISLATION OF RUSSIA AND POST-SOVIET COUNTRIES - Stepanyuk, Andrey; Volkov, Konstantin; Maslennikova, Liudmyla; Barinov, Andrey; Tychinin, Sergey (Revista Inclusiones, 2019)
The article deals with one of the compulsory methods of ownership right termination - the buy-out of pets if they are treated improperly. The authors draw attention to the specifics of this reason, which is associated with the buy-out subject, i.e. with an animal. They performed the comparative analysis of "pet improper treatment" and "cruel animal treatment" concepts, the problem of their differentiation is studied. They performed the comparative legal analysis of the legal regulation issues concerning the compulsory buy-out of pets in the civil legislation of the post-Soviet countries.